Influence of cognitive stimulation and physical exercise on sleep quality, mood and cognition in the elderly (Research, Society and Development, 2023)
This study investigated the relationship between cognitive stimulation and physical exercise on sleep quality, mood and cognitive functions in healthy elderly people. Sixty seniors of both genders were divided into three groups: Control Group – CG (n=20); Cognitive Stimulation Group – GEC (n=20) and Physical Exercise Group – GEF (n=20). The Epworth Sleepiness Scale (ESS); Pittsburgh Sleep Quality Index (PSQI-BR); Verbal Fluency Test (FAS); Digit Span and Brunel Mood Scale (Brums) were used as assessment instruments. Data were described as mean ± standard deviation and variables were compared using ANOVA for repeated measures, followed by Tukey's Post Hoc using SPSS version 12, considering p £ 0.05. The GEC showed less fatigue and greater vigor when compared to the GEF and GC (p  £ 0.05). In the assessment of executive function, the GEC's correct scores were significantly higher than the GEF and GC groups (p £ 0.05), with the GC having lower results than the GEF. In the memory assessment, the GEC showed higher scores in the direct order (p £ 0.05), reverse order (p £ 0.05) and sum of the orders (p £ 0.05) compared to the GEF and GC. There was lower latency to sleep onset among the GEC participants compared to the GEF and CG (p £ 0.05). Both the practice of cognitive stimulation and the regular practice of physical exercise can be used as a non-pharmacological strategy to help improve mood, cognition and sleep for the healthy aging process.